2011
DOI: 10.1103/physrevstper.7.020105
|View full text |Cite
|
Sign up to set email alerts
|

Moving toward change: Institutionalizing reform through implementation of the Learning Assistant model and Open Source Tutorials

Abstract: Florida International University has undergone a reform in the introductory physics classes by focusing on the laboratory component of these classes. We present results from the secondary implementation of two research-based instructional strategies: the implementation of the Learning Assistant model as developed by the University of Colorado at Boulder and the Open Source Tutorial curriculum developed at the University of Maryland, College Park. We examine the results of the Force Concept Inventory (FCI) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 31 publications
4
50
0
Order By: Relevance
“…16 and Q.7, as we found false positives for these questions in the interviews previously conducted, it is likely that the false-positive ratios of most other questions are lower. Hence, this study does not ignore other studies that have compared total FCI scores or evaluated FCI gain [21,22]. In the future, we might find the effect of the false positives on Q.16 and Q.7 relative to the total FCI score to be sufficiently small [23].…”
Section: Range Of Resultsmentioning
confidence: 99%
“…16 and Q.7, as we found false positives for these questions in the interviews previously conducted, it is likely that the false-positive ratios of most other questions are lower. Hence, this study does not ignore other studies that have compared total FCI scores or evaluated FCI gain [21,22]. In the future, we might find the effect of the false positives on Q.16 and Q.7 relative to the total FCI score to be sufficiently small [23].…”
Section: Range Of Resultsmentioning
confidence: 99%
“…Limited research on LA programs at FIU has been conducted. Research conducted on the physics LA program at FIU indicated that the implementation of LA programs along with open source tutorials have resulted in gains in student conceptual understanding in introductory physics courses (Goertzen, Brewe, Kramer, Wells, & Jones, 2011). Research on the LA program at FIU also indicated that physics, chemistry, and mathematics LAs are able to reflect on their teaching, as evident through their writing .…”
Section: Physics Las At Florida International Universitymentioning
confidence: 99%
“…Research on the LA program at Colorado indicate that the initiation of the program at UCB has increased the number of science majors entering education programs, resulted in greater learning gains for students enrolled in the courses using learning assistants (LAs), and impacted faculty by increasing their attention to student learning, use of collaborative student work, and use of students to transform their courses . Researchers at Florida International University (FIU) found that implementation of the Colorado LA program and use of open source tutorials resulted in greater student conceptual understanding in the introductory physics courses as determined by learning gains on an instrument designed to assess student conceptual understanding of forces (Goertzen, Brewe, Kramer, Wells, & Jones, 2011;Wells et al, 2009). Research at UCB also indicates that LAs themselves have stronger content knowledge after participation in the program and attitudinal gains demonstrating that their views about learning science became more expertlike .…”
Section: Benefits Of La Programsmentioning
confidence: 99%
“…For example, undergraduate students enrolled in LA-supported courses learn the subject matter better. 8,[11][12][13] Research has also documented important learning outcomes for the LAs themselves. LAs learn the subject matter better through teaching it, 8,12 LAs become better teachers, 14 and LAs solidify their identities as scientists.…”
Section: Introductionmentioning
confidence: 99%
“…8,[11][12][13] Research has also documented important learning outcomes for the LAs themselves. LAs learn the subject matter better through teaching it, 8,12 LAs become better teachers, 14 and LAs solidify their identities as scientists. 15 Additionally, university faculty in LA-supported courses become better teachers and begin to recognize their role in educational change.…”
Section: Introductionmentioning
confidence: 99%